A review of graphene-based broad bandwidth microwave absorbing textile-based composites in the low-frequency range. (2nd October 2022) - Aiqiong, Wang; Li, Jianxiong; Chen, Meng; Zhao, Xiaoming
The range and strength of Electromagnetic Wave loss are increasing with the development of electronic technology in intellectualization and diversification. Extensive research is focused on high-frequency microwave absorbersbut rarely on low-frequency ones. However, the shield of low-frequency microwave interference is bulky and complicated. It is necessary to adopt new structural composites with lightweight, porous, or multi-layer magneto-dielectric synergistic to obtain lighter, thinner, broader bandwidth, and strong absorption absorbers in the low-frequency range. The porous and multi-layer textiles would extend the Microwave (M. W.) transmitting pathway. The prepared M. W. textile-based composites possess broad bandwidth and strong absorption in the low-frequency range when magneto-dielectric synergistic functional particles have embedded in the textiles. This paper reviewed the modified graphene-based absorbers (GBAs), the hybrids combined GBAs with the low-frequency magnetic loss absorbers (LFMLAs), and the textile-based composites added by the complex combined GBAs with LFMLAs (GBAs/LFMLAs). The prepared GBAs/LFMLAs textile-based composites are broad bandwidth, lightweight, small thickness, and strong absorption materials in the low-frequency range. The prepared GBAs/LFMLAs textile-based microwave absorbers (MWAs) may expand the application scope of MWAs and promote their economic benefit. The GBAs/LFMLAs textile-based composites may propose a new strategy of broad bandwidth MWAs in the low-frequency range.